Pengaruh Aktivitas Fisik Intensitas Sedang terhadap Penurunan Kadar Glukosa Darah Sewaktu pada Laki-Laki Obesitas - Dian Syafitri; Khairun Nisa Berawi; Efrida Warganegara (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Obesity is a problem that concerns the world. The increasing of obese prevalence is relate to the risk of comorbidities that occurs through the insulin resistance mechanism. Moderate intensity physical activity can prevent insulin resistance and increase insulin sensitivity. The method is numerical comparative analytic research with a quasi-experimental design and the method of taking the repetitive measurement data (pre test - post test design) with a control group. Total of the samples are 30 people, divided into positive control groups (K1), negative control group (K2) and the treatment group (P). Analysis using Paired T-Test shows the value of p = 0.087 in group P1, p = 0.058 in group P2 and p = 0,000 in group P. Analysis using One Way Anova shows the value of p= 0.002 between P and K1, p= 0.085 between P and K2, p= 0.474 between K1 and K2. There is a statistically significant effect of moderate-intensity physical activity in the form of 30 minutes of brisk walking on lowering blood glucose levels in obese men. Keywords: Blood glucose level, insulin resistance, moderate intensity of physical activity, obesity.